2004
DOI: 10.1364/ol.29.002369
|View full text |Cite
|
Sign up to set email alerts
|

All-solid photonic bandgap fiber

Abstract: We describe the design and fabrication of a photonic bandgap fiber formed with two different glasses. As in a hollow-core fiber, light is guided in a low-index core region because of the antiresonances of the high-index strands in the fiber cladding. The structure described represents an ideal bandgap fiber that exhibits no interface modes and guides over the full width of multiple bandgaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
129
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(137 citation statements)
references
References 12 publications
3
129
0
5
Order By: Relevance
“…[3,4] Liquid crystals or flint glass [13] are candidates as high index materials for filling the cladding holes. The hole pitch and thus the hole diameter can be enlarged by using a high order bandgap.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…[3,4] Liquid crystals or flint glass [13] are candidates as high index materials for filling the cladding holes. The hole pitch and thus the hole diameter can be enlarged by using a high order bandgap.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Moreover, control of the fiber parameters during the drawing process is simpler and obtaining fiber parameters similar to the designed ones is straightforward (Buczynski et al 2012a, b). The development of ASPCFs has been reported by several groups (Feng et al 2003;Luan et al 2004;Buczynski et al 2012a, b) and successfully reported for supercontinuum generation (Kibler et al 2009;Wang et al 2012;Stepniewski et al 2014). Introduction of subwavelength inclusions in the core enables an additional degree of freedom in shaping of dispersion profile, while maintaining a constant value of effective mode area (Buczynski et al 2011).…”
Section: Introductionmentioning
confidence: 94%
“…The multicore fiber approach has the potential to produce photonic lanterns with a much larger number of modes in the system in a more straight forward manner. A multicore fiber with hundreds of cores can be fabricated in the same fashion as an all-solid photonic bandgap fiber [25], for example. Furthermore, the fabrication procedure for a multicore photonic lantern -one single fiber inside the low index jacket -is simpler and less prone to fabrication imperfections during the tapering process.…”
Section: Different Approachesmentioning
confidence: 99%